Effect of Phosphoric Acid (H3PO4) Activation on the Preparation of Activated Carbon from Gymnostoma Rumphianum Wood - Soenandar Milian Tompunu Tengker; Pamela Lumingas; Jeanne Maria Tuerah; Miftahul Jannah; Alfrie Musa Rampengan (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2025)
The utilization of Roya wood branches (RWB) as raw material for activated charcoal production has not yet been optimized in North Sulawesi, specifically in Wulauan Village, North Tondano District. This study aims to present the results of the analysis of the physical and chemical properties, X-Ray Diffraction (XRD), and Transmission Electron Microscope (TEM) of RWB-based activated charcoal. The production of activated charcoal was conducted in three stages: sample preparation, pyrolysis of RWB at a temperature of 365°C for approximately 3 hours, and activation of RWB charcoal using phosphoric acid (H₃PO₄) at concentrations of 1%, 2%, and 3% for 24 hours. The analysis of physical and chemical properties of both non-activated and H₃PO₄-activated RWB activated charcoal showed that the best quality was obtained at a 3% activator concentration, with a moisture content of 0.1683%, ash content of 2.3321%, volatile matter content (VMC) of 0.9429%, fixed carbon (FC) content of 96.7250%, and iodine adsorption capacity (IAC) of 10,535 mg/g, all of which meet the SNI 06-3037-1995 for activated charcoal. XRD analysis showed that non-activated RWB charcoal had three broad diffraction peaks in the ranges of 9–14°, 20–25°, and 35–50°, along with one sharp peak in the range of 25–30°. After activation with H₃PO₄, only three broad diffraction peaks were observed at 9–14°, 20–25°, and 35–50° for all three H₃PO₄ concentration variations.TEM analysis indicated that non-activated RWB charcoal had particle sizes ranging from 20–33 nm, while after activation with 1% H₃PO₄, the particle sizes ranged from 41–51 nm..